Penerapan Balanced Scorecard Sebagai Tolok Ukur Penilaian Kinerja Pada Perum Bulog Sub Divre Samarinda - AHMAD SYAULANI (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2016)
The purpose of this study to determine the performance Bulog Sub Division Samarinda when measured by the method of Balanced Scorecard. Balanced Scorecard test the performance of companies based on the financial perspective, customer perspective, internal business processes, learning and growth perspective. Collecting data through qualitative and quantitative methods. Qualitative namely by distributing questionnaires to customers and employees. Quantitative by using financial statements. The population in this study were all employees and customers Bulog Sub Division Samarinda. The sample in this study is 16 for employees and 38 customers. From the calculation of the four perspectives of the Balanced Scorecard can be seen overall value of 85.58. If measured by the size of the performance of the SOEs Decree No. Kep-100 / MBU / 2002 received ratings of AA with healthy criteria. It can become a passion for the company to improve its performance for the next year.Keywords: Performance, Balanced Scorecard, Performance Assessment.